Factors Associated With Initial Prasugrel Versus Clopidogrel Selection for Patients With Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention: Insights From the Treatment With ADP Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome (TRANSLATE‐ACS) Study. Issue 9 (September 2016) - Vora, Amit N.; Peterson, Eric D.; McCoy, Lisa A.; Effron, Mark B.; Anstrom, Kevin J.; Faries, Douglas E.; Zettler, Marjorie E.; Fonarow, Gregg C.; Baker, Brian A.; Stone, Gregg W.; Wang, Tracy Y.
Abstract : Background: Few studies have examined how antiplatelet therapies are selected during the routine care of acute myocardial infarction patients, particularly relative to the patient's estimated mortality and bleeding risks. Methods and Results: We examined patients presenting with acute myocardial infarction treated with percutaneous coronary intervention at 233 US hospitals in the TRANSLATE‐ACS observational study from April 2010 to October 2012. We developed a multivariable logistic regression model to identify factors associated with prasugrel selection. Prasugrel use rates and associated 1‐year risk‐adjusted major adverse cardiovascular events and Global Utilization of Streptokinase and t‐PA for Occluded Coronary Arteries (GUSTO) moderate/severe bleeding outcomes were also examined in relation to predicted mortality and bleeding using the validated Acute Coronary Treatment and Intervention Outcomes (ACTION) risk prediction scores. Among 11 969 patients, 3123 (26%) received prasugrel at the time of percutaneous coronary intervention. The strongest factors associated with prasugrel use included cardiogenic shock (odds ratio [OR] 1.68, 95% CI 1.25–2.26), drug‐eluting stent use (OR 1.45, 95% CI 1.31–1.62), and ST‐segment elevation myocardial infarction presentation (OR 1.23, 95% CI 1.12–1.35). Older age (OR 0.57, 95% CI 0.0.53–0.61), dialysis (OR 0.56, 95% CI 0.32–0.96), prior history of stroke/transient ischemic attack (OR 0.52, 95% CI 0.38–0.73), and interhospital transfer (OR 0.50, 95% CI 0.46–0.55) were associated with lowest prasugrel selection. Prasugrel was used less often than clopidogrel in patients at higher predicted bleeding risk (21.9% versus 29.7%, P <0.001). Yet paradoxically, prasugrel was also less likely than clopidogrel to be used in patients with higher predicted mortality risk (21.1% versus 30.2%, P <0.001). Adjusted bleeding and outcomes events were similar among those receiving prasugrel and clopidogrel in the 4 subgroups of patients based on bleeding risk and ischemic benefits. Conclusions: In community practice, prasugrel use may be driven more by bleeding risk rather than ischemic benefit. This may result in underutilization of higher potency ADP receptor inhibitor among patients more likely to derive ischemic benefit.